IDENTIFICATION OF MEFENAMATIC ACID ON HERBAL PRODUCTS IN CIMAHI AREA WITH THIN LAYER Chromatography (TLC) METHOD - Ellen Stephanie Rumaseuw; Krisna Pratama Putra Santoso (Jurnal Kesehatan, 2023)
Indonesian people use traditional medicines freely for alternative and complementary medicine. One of the traditional medicines consumed by the community is the herbal medicine for sore throat. Herbs that have good quality and pass safety tests can be widely produced by the pharmaceutical industry. Therefore, researchers want to conduct research on 5 herbal medicine products circulating in the Cimahi area. This study was conducted with the aim of knowing the herbal medicine for aches and paint circulating in the Cimahi area which contains the chemical drug mefenamic acid. The method used is thin layer chromatography with mobile phase : chloroform : ethyl acetate : glacial acetic acid ( 75 : 25 : 1 ) and silica gel Gf 254 as stationary phase. The results of this study prove that form the 5 product sample, there are 3 product sample that are suspected to contain mefenamic acid namely code A, C and E sample with the Rf values of 0,58, 0,55 and 0,78 respectively. Mefenamic acid has a standard Rf of 0,66 so that the 3 samples of herbal products are recommended not to be circulated and consumed by the public because they are not in accordance with the regulations of law no. 36 of 2009 concering health and regulation of the minister of health of the republic of Indonesia no. 007 of 2012 where both regulation prohibit the presence of chemical in traditional medicine.